2022
DOI: 10.1039/d2fo01384c
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol preserves antioxidant status and attenuates kidney fibrosis via modulation of TGF-β1/Smad signaling and inflammation

Abstract: Chronic kidney disease (CKD) with diverse aetiologies is emerging as a challenging kidney disorder associated with inflammation and interstitial fibrosis. Carvacrol (CVL) is a bioactive monoterpenoid found abundantly in oregano,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Besides the above molecules involved in fibrosis, reactive oxygen species (ROS) overproduction induced by UUO can promote inflammation, oxidative stress, and apoptosis, which contributes to fibrosis [36,37]. In this paper, we found a deficiency in the antioxidant capacity of UUO or CIN kidney, previous research found UUO induction resulted in impaired renal function along with the downregulation of antioxidant proteins, such as NRF2, NQO1 and SOD, as a result, more ROS produced finally leads to oxidative stress and fibrosis [38,39]. While the expression of SOD2, an antioxidant enzyme, can protect against chronic kidney injury and renal fibrosis by reducing oxidative stress in renal tubular cells [40,41].…”
Section: Discussionmentioning
confidence: 83%
“…Besides the above molecules involved in fibrosis, reactive oxygen species (ROS) overproduction induced by UUO can promote inflammation, oxidative stress, and apoptosis, which contributes to fibrosis [36,37]. In this paper, we found a deficiency in the antioxidant capacity of UUO or CIN kidney, previous research found UUO induction resulted in impaired renal function along with the downregulation of antioxidant proteins, such as NRF2, NQO1 and SOD, as a result, more ROS produced finally leads to oxidative stress and fibrosis [38,39]. While the expression of SOD2, an antioxidant enzyme, can protect against chronic kidney injury and renal fibrosis by reducing oxidative stress in renal tubular cells [40,41].…”
Section: Discussionmentioning
confidence: 83%
“…The canonical arm of the TGF-β pathway functions through adaptor proteins (Smad2, Smad3, and Smad4). TGF-β initiates the phosphorylation cascade of these proteins, forming a trimeric complex that migrates to the nucleus and transcribes various fibrotic genes [37]. Elevated expression of TGF-β and downstream signaling components have been reported in patients and murine DN models [8,38].…”
Section: Discussionmentioning
confidence: 99%